Programas de mejora genética de rumiantes menores basados en comunidades - Mueller, Joaquin Pablo (2017)
A recent revision of the state of knowledge, principles and examples of breeding programs described as community based (CBBP) indicates that such programs typically relate to low-input systems with farmers having a common interest to improve and share their genetic resources. CBBP are more frequent with keepers of small ruminants, in particular smallholders of local breeds, than with cattle, pigs or chickens, with which farmers may have easier access to genetic material and alternative breeding programs. Constraints on the adoption of conventional breeding technologies in low-input-systems cover a range of organizational and technical aspects. The analysis of seven CBBP with small ruminants located in countries of Latin-America, Africa and Asia highlights the importance of bottom-up approaches and involvement of farmers and local institutions in the planning and implementation stages. The analysis also reveals a high dependence of these programs on organizational, technical and financial support. Formal socio-economic evaluations of CBBP provide governments and other development agencies with the information necessary for up-scaling and outscaling successful experiences